Kinerja Usaha Pelayanan Jasa Alsintan (UPJA) Berdasarkan Balanced Scorecard di Provinsi Yogyakarta - Adi Prayoga; Kemal Mahfud; Irwanto Irwanto; Temy Temy Indrayanti (Jurnal Ilmu Pertanian Indonesia, 2024)
This study aims to evaluate the performance of the Alsintan Service Business (UPJA) in the Beginner class, Developing class, and Professional class. The research was conducted using survey techniques and analyzed descriptively and qualitatively using a balanced scorecard (BSC) approach. UPJA samples were determined purposively, namely UPJA that represents each class: UPJA Sumber Makmur as UPJA Professional class, UPJA OJHA as UPJA Beginner class in Sleman Regency, and UPJA Tirtosari as UPJA Developing class in Gunungkidul Regency. Respondents were UPJA managers and employees. The results showed that, based on the financial perspective, the performance of the UPJA Beginner class and UPJA Developing class was fairly good, while the UPJA Professional class was good. Based on the customer's perspective, UPJA's performance in all classes falls into the good category. Based on the perspective of internal business processes, the performance of the three UPJA classes has innovated the development of service business services and has carried out service business operations in the medium category. Based on the perspective of learning and growth, the performance of all UPJA classes already provides satisfactory facilities for their employees. However, the UPJA Beginner class and Developing class need to improve the ability of its operators through training. Keywords: agricultural machine tools service business, balanced scorecard, performance analysis, UPJA